Health status appraisal of women students and correlation with socio-academic outcomes - Patil, Kalpesh Ramdas; Gagarani, Manish Bansilal; Zanwar, Ankita Omprakash; Wani, Rajashree Bapusaheb; Yeole, Tejashree Dilip (Indian Journal of Community Health, 2014)
Background: Mental health is important factor for the maintenance of general health. According to experts of World Health Organization, health is a status of well-being of body, mind, society and not only the lack of disease. The purpose of study was to examine effects of associated factors on health status and academic performance of female students staying at hostel. The study aimed to establish correlations between various factors pertaining to health and academic performance of the students. Aim: To find out important predictors of academic performance & mental health of women students. Methods: The current study was an observational cross sectional study. The 373 female students taking pharmaceutical education were selected using systematic random sampling. The survey involved meetings of investigators with participants, explanation of study objectives to participants, filling of designed proforma and analysis of collected data. Results: Among 373 students; 247 (66.21%) were experienced homesickness initially, 56 (15.01%) students were homesick at the time of survey, while 70 (18.76%) students never experienced homesickness. The 85 (22.78%) students had poor, 212 (56.83%) students had average & 76 (20.37%) students had good academic performance. Majority of students (60.58%) were found to take measures for relieving stress. Out of 85 students having poor academic performance, 47 (55.29%) students were found to be mentally poor. Alternatively, among 152 students with poor mental health, 69 (45.39%) students had poor academic performance. Conclusion: Academic related stressors, victimization by tutors, relationship problems with parents and colleagues, homesickness due to staying away from families, conflicts between parents and hesitation to share personal problems with others were found to be important predictors of mental health problems & academic performance of women students.